2017
DOI: 10.4172/2161-0487.1000323
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Individuals with Hearing Loss: A Systematic Review

Abstract: Introduction: Hearing loss is a silent disability that reduces the hearing acuity of an individual and makes it difficult to perceive or interpret auditory signals. Persons with hearing loss are a heterogeneous group comprising of diverse and complex psychosocial characteristics of individuals who does not readily enjoy the empathy/sympathy received by other forms of disabilities that is readily visible. Hearing loss usually predisposes sufferers to resentment, hostility, rejection and subtle denial resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
3
21
1
1
Order By: Relevance
“…Spearman’s correlation proved the positive correlation among different variables taken under consideration including hearing loss type (hlt), age and hearing loss severity (hls) with depression, anxiety and stress. In addition to this, female seemed to developed symptoms of depression and anxiety more than male as shown in figure-2 and 3 as reported in literature 17…”
Section: Discussionsupporting
confidence: 68%
“…Spearman’s correlation proved the positive correlation among different variables taken under consideration including hearing loss type (hlt), age and hearing loss severity (hls) with depression, anxiety and stress. In addition to this, female seemed to developed symptoms of depression and anxiety more than male as shown in figure-2 and 3 as reported in literature 17…”
Section: Discussionsupporting
confidence: 68%
“…Early‐onset hearing loss in children can cause delay in speech development and language skills [4‐7]. Language skills are important for communication, and so difficulties in this area can have a cascading effect on emotional and social development, family interconnectedness, social inclusion and over all perceived quality of life [8‐10]. Consequently, children with early‐onset hearing loss are more likely to experience social isolation, low self‐esteem and depression [11‐14].…”
Section: Introductionmentioning
confidence: 99%
“…oppositional defiant disorder), and less consistently, anxiety and psychological distress [34‐39]. There is a lack of data from LMICs, even though these risks may be magnified due to a lack of hearing services or trained staff, little awareness about how to manage hearing loss [1], and higher levels of poverty, inequality and unemployment among people with hearing loss [9]. Therefore, the aim of this study was to conduct a systematic review of the peer‐reviewed literature from LMICs and summarise the evidence from studies that examined the link between hearing loss and mental health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies among children and adolescents with deafness have reported higher rates of mental health problems than their hearing counterparts [7]. For example, an Australian study assessed 99 children with bilateral deafness of at least 40 dB where parents and teachers completed the Strengths and Difficulties Questionnaire (SDQ) [9]. Results indicated that children with deafness scored significantly higher on the SDQ than their counterparts from normative samples according to both parents' and teachers' ratings [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an Australian study assessed 99 children with bilateral deafness of at least 40 dB where parents and teachers completed the Strengths and Difficulties Questionnaire (SDQ) [9]. Results indicated that children with deafness scored significantly higher on the SDQ than their counterparts from normative samples according to both parents' and teachers' ratings [9]. In another study of adolescents with deafness, 46% reported different types of mental health problems [10].…”
Section: Introductionmentioning
confidence: 99%